2020
DOI: 10.12659/msm.919300
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pre-Infarction Angina Combined with Mean Platelet Volume to Lymphocyte Count Ratio for No-Reflow and Short-Term Mortality in Patients with ST-Segment Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: The aim of the present study was to investigate the clinical predictive value of pre-infarction angina (PIA) combined with mean platelet volume to lymphocyte count ratio (MPVLR) for no-reflow phenomenon and shortterm mortality in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). Material/Methods: A total of 1009 STEMI patients who had undergone PCI were enrolled and subdivided into 4 groups based on the occurrence of PIA and the presence of MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Another study found that the level of MMP-9 in the culprit coronary artery in AMI patients was significantly higher in the no-reflow group than in the reflow group [57]. Kuliczkowski W. et al [58] also showed that patients with high MMP-9 levels are more likely to experience no-reflow, which is an independent factor in short-term mortality in patients with ACS [59]. There are also known studies proving the relationship between the occurrence of ventricular remodeling and a high level of MMP-9 in patients after ACS [60], which brings us to the potential benefit of determining the level of MMP-9 as a predictor of patient survival.…”
Section: Discussionmentioning
confidence: 96%
“…Another study found that the level of MMP-9 in the culprit coronary artery in AMI patients was significantly higher in the no-reflow group than in the reflow group [57]. Kuliczkowski W. et al [58] also showed that patients with high MMP-9 levels are more likely to experience no-reflow, which is an independent factor in short-term mortality in patients with ACS [59]. There are also known studies proving the relationship between the occurrence of ventricular remodeling and a high level of MMP-9 in patients after ACS [60], which brings us to the potential benefit of determining the level of MMP-9 as a predictor of patient survival.…”
Section: Discussionmentioning
confidence: 96%
“…We found significant differences in white blood cell count, mean corpuscular volume, red cell distribution width, mean platelet volume, serum glucose, and bicarbonate levels between the survivors and the non-survivors. In different cohorts, these characteristics have been shown to be related to either short- or long-term mortality in STEMI [10,16–20]. The high performance of the IMRS in cardiogenic patients appears to be secondary to its contents; thus, this score has a significant value for use in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current myocardial infarction (MI) risk scoring system is unable to detect the state of human inflammatory response. 2 …”
Section: Introductionmentioning
confidence: 99%